2012
DOI: 10.1177/030006051204000624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Natural Hirudin on Random Pattern Skin Flap Survival in a Porcine Model

Abstract: Local administration of hirudin can significantly increase the surviving area in overdimensioned random pattern skin flaps, in a porcine model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Ying‐Xin et al reported increased survival in compromised free flaps in rats after subdermal injections of both natural or recombinant hirudin compared to controls injected with saline (Ying‐Xin et al, ). Similarly, increased survival of surface area of compromised random pattern skin flaps after local subdermal injection of natural hirudin compared to controls have been reported in the porcine models (Guo‐Qian et al, ; Zhao et al, ). Furthermore, intravenous injection of recombinant hirudin in regional flaps in rabbits has been reported to increase surface area survival compared with injection of low molecular weight heparin or no injection (Duzgun et al, ).…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Ying‐Xin et al reported increased survival in compromised free flaps in rats after subdermal injections of both natural or recombinant hirudin compared to controls injected with saline (Ying‐Xin et al, ). Similarly, increased survival of surface area of compromised random pattern skin flaps after local subdermal injection of natural hirudin compared to controls have been reported in the porcine models (Guo‐Qian et al, ; Zhao et al, ). Furthermore, intravenous injection of recombinant hirudin in regional flaps in rabbits has been reported to increase surface area survival compared with injection of low molecular weight heparin or no injection (Duzgun et al, ).…”
Section: Discussionmentioning
confidence: 64%
“…Previous work reports the use of recombinant or natural hirudin in the treatment of venous congestion in animal models (Duzgun et al, ; Guo‐Qian et al, ; Ying‐Xin et al, ; Zhao et al, ). Ying‐Xin et al reported increased survival in compromised free flaps in rats after subdermal injections of both natural or recombinant hirudin compared to controls injected with saline (Ying‐Xin et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations